2018
DOI: 10.1159/000491568
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation of KIF11 in a Child with 22q11.2 Deletion Syndrome Associated with MCLMR

Abstract: Microcephaly with or without chorioretinopathy, lymphedema, or mental retardation (MCLMR; OMIM 152950) is a rare autosomal dominantly inherited syndrome. Mutations in the kinesin family member 11 (KIF11) gene have been associated with this condition. Here, we report a de novo novel heterozygous missense mutation in exon 12 of the KIF11 gene [c.1402T>G; p.(Leu468Val)] in a boy with 22q11.2 microdeletion syndrome. His major features were microcephaly, ventricular septal defect, congenital lymphedema of the feet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…KIF11 serves an essential role in cell mitosis ( 22 ) and the transport of secreted proteins ( 23 ). It has been demonstrated that KIF11 mutation causes autosomal dominant familial exudative vitreoretinopathy, as well as microcephaly, with or without choroidal retinopathy, lymphedema or hypophrenia ( 24 , 25 ). KIF11 acts as an oncogene in tumors and is associated with a poor prognosis in breast cancer ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…KIF11 serves an essential role in cell mitosis ( 22 ) and the transport of secreted proteins ( 23 ). It has been demonstrated that KIF11 mutation causes autosomal dominant familial exudative vitreoretinopathy, as well as microcephaly, with or without choroidal retinopathy, lymphedema or hypophrenia ( 24 , 25 ). KIF11 acts as an oncogene in tumors and is associated with a poor prognosis in breast cancer ( 26 ).…”
Section: Introductionmentioning
confidence: 99%